Choosing between the truth and rights: dilemma of a qualitative researcher - Hussien, Suhailah; Rais, Haniza (2015)
Making group work works in a classroom could be challenging not only in the attainment of the objectives or results of the group work, but also of the whole process. My study on the use of group work among pre service teachers was initially aimed to explore their experiences and understanding of group work as a process of learning and teaching. The phenomenological study involved an undergraduate skill based course, consisted of twelve final year female students. The students were given the task to organize a field trip to an orphanage. They were provided with guidelines in planning and managing the trip, after which they were required to write a report. Students also documented their experience in journal. Students’ reports and journals were analysed and three broad themes emerged, which were group work as a constructive pedagogy, as a process of development or learning, and the challenges of group work in the form of group dynamics. However, the third theme, which is, the intra and inter group relations and interactions, cornered me in a situation where I found myself in a dilemma to present either the truth (results) of the study or to maintain the rights of the participants. This paper discusses how I managed my dilemma through the negotiation of my roles as the researcher and course instructor. At the same time, I was compelled to redefine the boundaries of the study with the participants’ consent. This paper reveals that a researcher’s readiness to return to the field and to the participants is imperative in our attempt to ensure that the ethical issues of a research are carefully attended.